A content analysis of a 1950s residential film location as a design narrative of Filipino values - Cena, Catherine J.
The research primarily dealt with the importance of Filipino values to residential interior design, observed "in-action" through film. It attempted to answer the following questions: What design narrative components are present in the location of the 1950s film 'Biyaya ng Lupa'? How do the design narrative components relate to the social, economic and cultural values reflected in the film? The research utilized descriptive content-analysis wherein the film was read as text, based on the Design as Narrative theory (Ganoe 1). The research used a combination of quantitative and qualitative approaches. The selection of the sample used for the study was purposive. The film selected is Filipino-made circa 1950s, entitled 'Biyaya ng Lupa', directed by Manuel Silos. It showed a family residence throughout the span of approximately 20 years, with the interior of the location a significant part of the narrative. The film portrays the lives of a simple, rural family living in their equally simple residence. Content analysis of design narrative components found in the film - which include order, experience, state of mind, meaning, transformation, multiplicity, and convergence (Ganoe 11-12) - was performed. Text analysis wherein the film becomes the text analyzed was also used to identify the design narrative components in relation to personal, socio-economic and cultural values of Filipinos. Ocular observation was used to note down the visual details of the film using an observation guide. The observation guide was used to ensure structured observation. The data gathered through content analysis, text analysis and ocular observation were summarized and tabulated through matrices and pie charts. The results were analyzed using the components of design narrative in order to identify personal, socio-economic and cultural values, of the characters in the film, 'Biyaya ng Lupa'. Categories and themes were derived and analyzed using frequency and chronological order. The components of design narrative applicable to the film, 'Biyaya ng Lupa' are order, experience, state of mind, meaning, transformation, multiplicity, universality and convergence. These components deal with specific salient design issues that reveal the relationship between Filipino values and the interior design of the residence of the characters. These Filipino values are grouped into three categories: personal and family, socio-economic, and cultural values. Personal and family values include family unity, marriage, love for children, respect for authority, privacy, authority, care for the impaired, and spiritual needs. Socio-economic values include belonging to the rural middle class, family hierarchy and gender roles. Cultural values include hope, the Filipino identity, a male dominated belief, societal dependency and religiosity. A direct relationship between these Filipino personal and family values, socio-economic values and cultural values and residential interior design was revealed. It suggests that the values of the users of the residence analyzed affected and somehow dictated the interior design of the location. It is recommended that designers become aware of the importance of Filipino values, socio-economic values, and cultural values derived from the analysis of experience, background and beliefs affect residential design and vice versa.